Maternal and cardiac output response to vasopressor therapy during spinal anaesthesia for Caesarean Section in severe preeclampsia - Daniels, Abigail Hanlise (Department of Anaesthesia, 2018)
Background: The maternal haemodynamic responses to vasopressors during spinal anaesthesia for caesarean delivery in patients with severe preeclampsia, have not been accurately described. This study compared the haemodynamic effects of the vasopressors ephedrine and phenylephrine during spinal anaesthesia. Methods: Thirty nine women with treated severe preeclampsia presenting for spinal anaesthesia for caesarean section for a maternal indication, were studied. Baseline maternal haemodynamics were measured in the left lateral position, using minimal invasive cardiac output monitoring (LiDCOrapid). A 300 mL colloid preload was then administered. After standard spinal anaesthesia, 20 patients whose mean arterial pressure decreased to a predetermined target value were randomised to 2 groups of 10, to receive an initial bolus of either 7.5 mg ephedrine or 50 μg phenylephrine, and the haemodynamic responses recorded. The primary outcome was the percentage change in cardiac index. Results: Spinal hypotension in 20 patients was associated with an increase in mean cardiac output from baseline (mean difference 0.7 L/min, p<0.0001). In response to vasopressor, the mean [SD] percentage change in cardiac index was greater, and negative, in patients receiving phenylephrine versus ephedrine (-12 [7.3] vs 2.6 [6] L/min respectively, p=0.0001).] L/min respectively, p=0.0001). Post-vasopressor mean percentage change [SD] in heart rate and systemic vascular resistance (SVR) were higher in patients receiving phenylephrine (-9.1 [3.4] vs 5.3 [12.6], p=0.0027, and 22.3 [7.5] vs -1.9 [10.5] %, p<0.0001 respectively). Conclusions: Phenylephrine effectively reverses spinal anaesthesia-induced haemodynamic changes in severe preeclampsia, if left ventricular function is preserved.